Analytical and experimental study of hydrodynamic and hydroacoustic effects of air injection flow rate in ventilated supercavitation. (1st February 2015) - Nouri, Nowrouz M.; Riahi, Mohammad; Valipour, Ali; Raeyatpishe, Mohammad M.; Molavi, Esmail
Abstract: Formation of supercavity around an underwater vehicle improves the hydrodynamic performance of fluid flow and causes vehicle to reach higher speeds. However, sound generated by the supercavitation is very effective in recognition of the vehicle and reduction in its controlled precision. In this study, compressible Navier–Stocks equations were solved by using the method of Large Eddy Simulation and combining them with the physical source and sink model to simulate supercavitation flow numerically. The qualitative and quantitative parameters from numerical results compared and confirmed with experimental results. Subsequently, by considering a suitable control surface around the simulated supercavity, the needed parameters for acoustic analysis were provided. Eventually, by solving the hybrid hydroacoustic model presented by Riahi et al. the far field noise of supercavity was estimated. In light of important role of air injection flow rate in the formation of ventilated supercavity, hydrodynamic and hydroacoustic results for three different lengths of supercavity stemmed by different air injections, were compared with each other. According to the obtained results, acoustic behavior of the supercavity was changed by increasing of air injection. Highlights: We used mathematical models obtained from perturbation method to simulate hydrodynamic and hydroacoustic of supercavitation flow. The physical source and sink model suggested by Nouri was used for simulation of supercavity. We validated quantitative and qualitative numerical results by experimental results. Sound generated by supercavity was predicted by using hybrid method. In low flow rate ventilation, dipole source intensity is higher than other sources.